An autoregulatory feedback loop between Mdm2 and SHP that fine tunes Mdm2 and SHP stability - Yang, Zhihong (2012)
Mdm2 is a crucial negative regulator of the tumor suppressor function of p53. However, little is known about Mdm2 protein stability regulation by other tumor suppressors. Nuclear receptor small heterodimer partner (SHP, NROB2) functions as a tumor suppressor in liver cancer. We show here a surprising finding of a feedback regulatory loop between SHP and Mdm2. SHP stabilizes Mdm2 protein by abrogating Mdm2 self-ubiquitination, and Mdm2 in turn attenuates SHP protein levels under p53-deficient conditions. Such cross-regulation critically depends on the physical interaction of SHP with Mdm2 through the SHP K170 residue. The Mdm2-SHP interplay represents a novel component of Mdm2 signaling that is likely to dictate Mdm2 activity and function.